Molecular Phylogenetic Support to the Resurrection of Pareas macularius from the Synonymy of Pareas margaritophorus (Squamata: Pareidae) - Suntrarachun, Sunutcha; Chanhome, Lawan; Hauser, Sjon; Sumontha, Montri; Kanya, Kirati (Tropical Natural History, 2020)
The taxonomy of the Asian snail-eating snakes in the genus Pareas Wagler, 1830 has been an ongoing controversy. Recently suggested taxonomic changes included the synonymization of Pareas macularius Theobaldi, 1868 with Pareas margaritophorus (Jan in Bocourt, 1866), and subsequent resurrection of P. macularius as a valid species on the basis of morphological data for more than 60 specimens from northern Thailand and the holotypes of both species. To confirm the validity of P. macularius, we analyzed mitochondrial DNA sequences data for 14 bicolored and spotted snail-eaters from Thailand (morphologically identified as either P. macularius or P. margaritophorus). The results strongly supported the validity of P. macularius as a species distinct from P. margaritophorus.